2017
DOI: 10.1039/c6ra27282g
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of anhydro-aldose tosylhydrazones with hydroxy compounds and carboxylic acids: a new route for the synthesis of C-β-d-glycopyranosylmethyl ethers and esters

Abstract: Cross couplings of O-peracylated 2,6-anhydro-aldose tosylhydrazones (C-(b-D-glycopyranosyl) formaldehyde tosylhydrazones) with alcohols, phenols, and carboxylic acids were studied under thermic or photolytic conditions in the presence of K 3 PO 4 or LiOtBu. The reactions failed with EtOH, BnOH, or tBuOH, however, (CF 3) 2 CHOH, electron poor phenols and carboxylic acids gave the corresponding C-b-D-glycopyranosylmethyl ethers and esters, respectively, representing a new access to these glycomimetic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…As a part of a program targeting the systematic study of applications of anhydro-aldose tosylhydrazones (compounds H in Scheme 1) as coupling partners in metal-free [4,5] and transition metal-catalyzed coupling reactions we have been interested in the Pd-catalyzed coupling of H with bromobenzenes. According to general mechanistic considerations, such coupling reactions [6][7][8] are expected to result in substituted exo-glycals (compounds E in Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…As a part of a program targeting the systematic study of applications of anhydro-aldose tosylhydrazones (compounds H in Scheme 1) as coupling partners in metal-free [4,5] and transition metal-catalyzed coupling reactions we have been interested in the Pd-catalyzed coupling of H with bromobenzenes. According to general mechanistic considerations, such coupling reactions [6][7][8] are expected to result in substituted exo-glycals (compounds E in Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Their NMR study clearly showed the 4 C 1 conformation of the ring and the a(D) anomeric conguration which can be explained by the anchimeric effect of the 2-O-acyl substituent and also corresponds to the anomeric effect of the CN substituent forcing this group to occupy an axial position. [38][39][40] Subsequently cyanides 2 were transformed into the tosylhydrazones 3 under reductive conditions in the presence of tosylhydrazine, which on deprotonation by K 3 PO 4 41 (instead of the less easily handled NaH 34 ) and heating to reux temperature gave exo-mannals 4. The pyranoid ring of tosylhydrazones 3 and exo-mannals 4 had a 5 C 2 conformation according to the 3 J coupling constants between H-2, H-3, H-4, H-5 and H-6 ( Table 1).…”
Section: Synthesis Of Exo-mannal Derivativesmentioning
confidence: 99%
“…With phenols 80 were formed in moderate yields (Entry 3). In the reactions with carboxylic acids the yields of 80 increased to give the best results with sugar derived acids (Entries 4-6) [105]. The glycosylmethyl sulfides 76 were obtained in moderate and good yields with aliphatic thiols and thiophenols, respectively (Entries 7 and 8) [106].…”
Section: Syntheses Of Other Glycomimetics and Their Precursorsmentioning
confidence: 99%